First symptom guides diagnosis and prognosis in neurodegenerative diseases—a retrospective study of autopsy proven cases. (22nd March 2021) - Vöglein, Jonathan; Kostova, Irena; Arzberger, Thomas; Roeber, Sigrun; Schmitz, Peer; Simons, Mikael; Ruf, Viktoria; Windl, Otto; Herms, Jochen; Dieterich, Marianne; Danek, Adrian; Höglinger, Günter U.; et al.
Abstract: Background and purpose: Clinical diagnostic criteria for neurodegenerative diseases have been framed based on clinical phenomenology. However, systematic knowledge about the first reported clinical symptoms in neurodegenerative diseases is lacking. Therefore, the aim was to determine the prevalence and clinical implications of the first clinical symptom (FS) as assessed by medical history in neuropathologically proven neurodegenerative diseases. Methods: Neuropathological diagnoses from the Neurobiobank Munich, Germany, were matched with clinical records for analyses of the diagnostic and prognostic values of FSs. Results: In all, 301 patients with the neuropathological diagnoses Alzheimer disease (AD), progressive supranuclear palsy (PSP), frontotemporal lobar degeneration (FTLD), Lewy body disease (LBD) including the neuropathologically indistinguishable clinical phenotypes Parkinson disease and dementia with Lewy bodies, multiple system atrophy (MSA) and corticobasal degeneration (CBD) were studied. Memory disturbance was the most common FS in AD (34%), FTLD (19%) and LBD (26%), gait disturbance in PSP (35%) and MSA (27%) and aphasia and personality changes in CBD (20%, respectively). In a model adjusting for prevalence in the general population, AD was predicted by memory disturbance in 79.0%, aphasia in 97.2%, personality changes in 96.0% and by cognitive disturbance in 99.0%. Gait disturbance and tremor predicted LBD in 54.6% and 97.3%, coordination disturbance MSA in 59.4% and dysarthria FTLD in 73.0%. Cognitive FSs were associated with longer survival in AD (12.0 vs. 5.3 years; p < 0.001) and FTLD (8.2 vs. 4.1 years; p = 0.005) and motor FSs with shorter survival in PSP (7.2 vs. 9.7; p = 0.048). Conclusions: Assessing FSs in neurodegenerative diseases may be beneficial for accuracy of diagnosis and prognosis and thereby may improve clinical care and precision of study recruitment. Abstract : In this work, the distribution of first clinical symptoms in neurodegenerative diseases is provided together with a prevalence adjusted model that depicts the probabilities for each neurodegenerative diagnosis if a distinct first symptom occurs in a patient. For clinicians that hover between two neurodegenerative diagnoses, a scheme is given that may facilitate diagnosis using the first clinical symptom. Further, the prognostic value of the first clinical symptom regarding survival in neurodegenerative diseases is analyzed.